Virality in Social Media Advertising: A Case Study in Bandung Tourism - Romadhoni, Riefky Amarullah; Siallagan, Manahan; Mayangsari, Lidia (School of Business and Management Institut Teknologi Bandung, 2019)
Abstract. The growth of tourism in Indonesia makes Bandung, as one of the major cities in Indonesia, has to improve its tourism even further. One of the plans of the Department of Tourism and Cultural Bandung is about how to advertise tourism in Bandung City. The current state of Bandung Tourism Ambassador advertisement is through social media Instagram by using her intuition. This research proposes a new system to help Bandung City promotes its tourism destination by using STEPPS (Socio-currency, Trigger, Emotion, Public, Practical Value, Story) factors and service-dominant logic approach. By analysing the value of each factor, the advertiser can determine which words and topic that can make the advertisement viral and more engaging, thus boosting the popularity of Bandung tourism.Keywords: Bandung city tourism, content analysis, STEPPS, service science